A GESTÃO DO AGENTE AMBIENTAL RUÍDO: ANÁLISE CRÍTICA EM UMA UNIDADE MARÍTIMA DE PRODUÇÃO DE PETRÓLEO - Araújo Filho, Nelson Costa (2005)
Health, Comfort and Operational Efficiency are factors directly linked to the acoustic quality of the several existing environments in an offshore oil production platform. The difficulty in designing and implementing noise reduction measures shows us that the problem is complex and involves several phases, from the preliminary acoustic prediction, during the basic project stage, the generation of solid documentation, charging of the equipments suppliers and those responsible for the detailing and construction of oil rigs, to the final phase of acceptance and measuring. This study aims at discussing noise control management through the analysis of a case study of an offshore platform, drawing a parallel with the practices proposed by some normative bodies, like NORSOK and ISO, in order to better control this aggressive agent. It also discusses some aspects of the general administrative theory, pinpointing the critical factors for successfully managing conflicts which are inherent to the structural and organizational aspects of the enterprise. As a conclusion, the author proposes the implementation of a series of measures, both in the technical and occupational fields, which are translated into suggestions for the improvement of the whole process involved in noiserelated project analysis management.